Optimisation of culture diagnostic conditions and evaluation of a molecular assay for the detection of Shigella species from diarrhoeagenic stool specimens - Nadan, S. (University of Pretoria, 2023)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2022.